DIGITAL CUSTOMER SERVICE: THE EFFECTIVENESS OF COMMUNICATION IN TECHNOLOGY REVOLUTION 4.0 - Alya Reizanda Bakari; Catherine Hellen Christina; Davina Putri Ninditya; Muhammad Iffan (Universitas Komputer Indonesia, 2021)
The development of technology has changed the way of interpersonal communication into digital communication. Technological speed can be in the form of technology applications, computers, social media, robots and the public environment. Digital customer service is one of the creative innovations and practical solutions to self-service with new technologies found in the current digital revolution 4.0. Effectiveness is a goal or success in achieving goals or objectives based on what has been set. The effectiveness of communication can be seen based on the effectiveness of the message received and can be understood by the customer. The purpose of this study was to determine the effectiveness of digital Customer Service as an example of the 4.0 communication technology revolution in helping its use to get maximum service. This research uses qualitative research methods with descriptive studies. While the concept used is the effectiveness of communication from Andre Hardjana. The results of this study are the effectiveness of communication in the application of digital customer service in the community with new technology. This research was conducted to determine the effectiveness of communication in the application of digital customer service in the midst of the communication transition of the digital revolution 4.0.